DEVELOPING CHARACTER BASED STORYBOOKS FOR TEACHING ENGLISH FOR THE FIFTH GRADE STUDENTS AT SDN 4 BANYUASRI IN THE ACADEMIC YEAR OF 2016/2017 - ., Desi Nursari Andayani; ., Dra. Luh Putu Artini, MA., Ph.D.; ., I Nyoman Pasek Hadi Saputra, S.Pd., M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
The objectives of this study were (1) to develop character based storybooks to supplement the character education in English classes for the fifth grade students at SDN 4 Banyuasri and (2) to analyze the quality of the developed character based storybooks for teaching the fifth grade students at SDN 4 Banyuasri. The type of this study was developmental research which use Hannafin and Peck (1988) instructional design model. There were three phases in this study including need analysis, design, and development/implementation. In testing stages, the products were validated through a review by the experts. The instruments used to collect the data in this study were observation, interview guide, and questionnaire. The results of the study were (1) the developed storybooks were a simple cause and effect story which contained moral value messages which taught hard working and discipline character. (2) The mean score of the expert judgments for the developed storybooks was in range 4.73 – 4.95. According to quantitative data conversion which proposed by Suharto (2006), the quality of the product of the research could be categorized as very good. This means that the storybooks are ready for implementation in the classes.Kata Kunci : character education, media development, storybook Penelitian ini bertujuan untuk (1) mengembangkan buku cerita berbasis karakter untuk melengkapi pendidikan karakter dalam pelajaran bahasa Inggris untuk kelas 5 di SDN 4 Banyuasri dan (2) mengevaluasi kualitas dari buku cerita yang dikembangkan untuk mengajar bahasa Inggris untuk kelas 5 di SDN 4 Banyuasri. Jenis penelitian ini adalah penelitian dan pengembangan yang model pengembangan dari Hannafin dan Peck (1988). Ada tiga fase dalam penelitian ini yaitu, need analysis, design, dan development/implemetation. Dalam tahap evaluasi, produk yang dikembangan divalidasi oleh para ahli. Instrumen yang digunakan untuk mengumpulkan data pada penelitian ini adalah panduan observasi, panduan wawancara, dan kuesioner. Hasil penelitian ini adalah (1) Buku cerita yang dikembangkan adalah cerita sebab dan akibat yang simple yang memiliki pesan tentang nilai moral yang dapat digunakan untuk mengajarkan karakter disiplin dan kerja keras. (2) nilai rata-rata dari penilaian para ahli untuk buku cerita yang dikembangkan berada di kisaran 4.20 – 5.00. Berdasarkan quantitative data conversion dari Suharto (2006), kualitas dari hasil dari penelitian ini bisa dikategorikan sebagai very good media. Ini berarti buku cerita yang dikembangkan bisa dimplementasikan di kelas.keyword : pendidikan karakter, pengembangan media, buku cerita